2022
DOI: 10.1039/d1nj05998j
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol/hydroxypropyl-β-cyclodextrin inclusion complex: structure analysis, release behavior, permeability, and bioactivity underin vitrodigestion

Abstract: Cannabidiol (CBD), a natural phenolic compound, has many promising biological activities, but its use in food or other fields is restricted owing to inferior water solubility. So hydroxypropyl-β-cyclodextrin (HP-β-CD) was...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…For the exterior hydrophilic surface of CDs, inclusion complexes could have a good wettability, which improved the water solubility of the poorly soluble drugs. This result was consistent with the results of inclusion complexes of cannabidiol with β-cyclodextrin [ 32 ].…”
Section: Resultssupporting
confidence: 93%
“…For the exterior hydrophilic surface of CDs, inclusion complexes could have a good wettability, which improved the water solubility of the poorly soluble drugs. This result was consistent with the results of inclusion complexes of cannabidiol with β-cyclodextrin [ 32 ].…”
Section: Resultssupporting
confidence: 93%
“…The molar stoichiometry of the CBD and β-CD complex was 1:2 by the precipitation method in which only 7 mg of β-CD was required to complex 1 mg of CBD ( Mannila et al, 2007 ). However, Li et al (2022) reported CBD was inclusion complexed with hydroxypropyl-β-CD at a ratio of 1:1.…”
Section: Resultsmentioning
confidence: 99%
“…Macrocyclic receptors are the major workhorses in supramolecular chemistry. During the past few decades, a number of novel supramolecular macrocycles have emerged, such as crown ethers, [23][24][25][26][27][28][29] cyclodextrins, [30][31][32][33][34][35] calixarenes, [36][37][38] cucurbiturils, [39][40][41][42][43] pillararenes, [44][45][46][47][48][49][50] coronarenes, 51 cyclophanes 52 and others, [53][54][55][56][57] greatly enriching the toolkit of supramolecular chemists. Biphen[n]arenes, [58][59][60]68 including basic biphen[n]arenes, functional biphen[n]arenes, and cage compounds, are new macrocyclic hosts that appeared in the supramolecular world recently.…”
Section: Introductionmentioning
confidence: 99%